BASIC CONCEPTS OF INFECTIOUS DISEASES AND INFECTIONS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
This article examines the importance of the spread of infections among people today and measures to prevent its spread. Epidemiological features of the infectious disease, spread factors and diagnostic methods were analyzed in the study. Emphasis is placed on effective measures to prevent infectious diseases, including implementation of vaccination programs, compliance with sanitary and hygiene rules, and raising public awareness. The article describes strategies to prevent infectious diseases.